Optimal Grounding Grid Design in Power System Substation by Multi-Objective Optimization NSGA-II - เจริญวงค์ ประสงค์; บัวใหญ่ กฤติเดช; เกิดชื่น กาณฑ์ (RMUTL Engineering Journal, 2019)
This paper presents the design of the grounding system in the power station using a multi-objective optimization using NSGA-II. (NSGA: Non-dominated Sorting Genetic Algorithm) The Grounding systems in power stations must be safe and electrical equipment and must be economical. The objective function of finding the right value consists of the price of the material, installation wages and security conditions. In addition, the multi-objective optimization using NSGA-II is also adjusted in line with the acceleration time for the problem. The results showed that such an approach can solve the problem well. The grounding grid design in power system substation can be designed economically and safely. This article also tests the design of the grounding system of a real power station and compares the results with the most appropriate GA (Genetic Algorithm) and PSO. (Particle Swarm Optimization)